Representations of Human and Environmental Vulnerability in North American Literature. - Chapman, Ana María; Bennett, Lucía (Editorial Universidad de Sevilla, 2022)
Since the 9/11 attacks on the World Trade Center somberly inaugurated the new millennium, critical discourses on trauma, grieving and vulnerability have gained relevance in the academic sphere. The global dimension of these events was however based on their mediatic repercussions worldwide, rather than on the actual physical impact that they had on the world population. Throughout the following two decades of the twenty-first century, intersecting environmental, economic and technological developments into globalization are revealing a heightened awareness of a similarly global vulnerability that visibilize embodied forms of ongoing trauma, public grieving and structural oppression of precarious life forms and environmental conditions. These stand against the backdrop of the Fourth Industrial Revolution (4th IR), which is ambiguously put forward as either the origin or solution of this situation. The last two years of pandemic have intensified the interdependence of virtual connection and social alienation/exclusion relating techno-digital hyperconnectedness and embodied forms of existence, giving a new sense to the concept of “risk society” developed at the turn of the century (Beck 1992; Giddens 1998). This special issue critically explores the forms of human and environmental vulnerabilities that are generated in the context of the 4th IR, including vulnerable forms of human and non -human intersubjectivity such as online embodied (onlife) interfaces or “inforgs” (Maynard 2015), precarious life and working conditions resulting from the global dimension of the 4th IR, environmental forms of vulnerability in the 4th IR, the role of the pandemic in raising awareness about global vulnerability, or the hierarchical naturecultures (Haraway 2003) emerging from transhumanist ethics.
Keywords: Literatura norteamericana; FIlosofía; Fourth Industrial Revolution; Posthumanism; Vulnerability studies